2017
DOI: 10.1001/jamaophthalmol.2016.5399
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical Activity and Medicare Payments for Female vs Male Ophthalmologists

Abstract: The number of women in ophthalmology is rising. Little is known about their clinical activity and collections.OBJECTIVE To examine whether charges, as reflected in reimbursements from the Centers for Medicare & Medicaid Services (CMS) to ophthalmologists, differ by sex and how disparity relates to differences in clinical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 21 publications
(35 reference statements)
4
71
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24] Our findings also echo recent Medicare data from the United States, where American female ophthalmologists earn less and made fewer clinical billings than their male counterparts. 7 In this study, since we found that fees per service were similar between females and males, this disparity in income may be due to our findings of the longer duration of time females spent on consultations. We also found that females provided a higher number of paediatric consultations per clinician, which tend to be longer in duration than adult consultations.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24] Our findings also echo recent Medicare data from the United States, where American female ophthalmologists earn less and made fewer clinical billings than their male counterparts. 7 In this study, since we found that fees per service were similar between females and males, this disparity in income may be due to our findings of the longer duration of time females spent on consultations. We also found that females provided a higher number of paediatric consultations per clinician, which tend to be longer in duration than adult consultations.…”
Section: Discussionmentioning
confidence: 57%
“…1,2 In 2017, 21.2% of fellows and 35.1% of ophthalmology trainees were female in the Royal Australian & New Zealand College of Ophthalmologists (RANZCO). 3 Studies around the world have found that female doctors earn less than their male counterparts, even after accounting for number of hours worked, [4][5][6][7][8] and female ophthalmologists report doing less procedural work than their male counterparts. 9,10 Few studies have been conducted investigating the differences in practice patterns, social circumstances and remuneration between female and male ophthalmologists in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…9 Gender differences are apparent in ophthalmology careers as well, as female ophthalmologists submitted on average 936 fewer charges annually than males to Medicaid, even after accounting for time spent on clinical activity. 10 This difference resulted in females earning $0.56 for every dollar earned by a male in 2012 and 2013. 10 Female ophthalmologists also have fewer industry ties and receive less industry payments than male counterparts.…”
mentioning
confidence: 99%
“…10 This difference resulted in females earning $0.56 for every dollar earned by a male in 2012 and 2013. 10 Female ophthalmologists also have fewer industry ties and receive less industry payments than male counterparts. 11 There is a need to expand the understanding of how gender may affect ophthalmology residency training.…”
mentioning
confidence: 99%
“…The event is not only a first for this journal but a first for any Clarivate Analytics Quartile 1‐ranked general ophthalmology journal, including Ophthalmology , JAMA Ophthalmology , British Journal of Ophthalmology and Acta Ophthalmology , none of which have ever had a woman Editor‐in‐Chief. Gender inequality in ophthalmology has been highlighted in multiple recent articles from different countries, in this journal and others, relating to a range of professional factors, including reimbursement, journal article authorship and general experiences in the workplace . Analysis and identification of the problem is the first step to addressing gender inequality, as promoted by the Athena Scientific Women's Academic Network (SWAN) initiative for gender equity in science (https://www.sciencegenderequity.org.au).…”
mentioning
confidence: 99%